2020
DOI: 10.1002/arch.21651
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of DNA methyltransferase 1 and its role in temperature change of armyworm Mythimna separata Walker

Abstract: DNA methylation refers to the addition of cytosine residues in a CpG context (5′‐cytosine‐phosphate‐guanine‐3′). As one of the most common mechanisms of epigenetic modification, it plays a crucial role in regulating gene expression and in a diverse range of biological processes across all multicellular organisms. The relationship between temperature and DNA methylation and how it acts on the adaptability of migratory insects remain unknown. In the present work, a 5,496 bp full‐length complementary DNA encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In the present study, the first 3 days of cold exposure were marked with a significant decrease in the expression levels of all the Dnmt genes but increased significantly with the prolongation of days of cold treatment. A similar trend was observed in the armyworm (Mythimna separata) where a decreased pattern of expression was observed after short exposures to various temperatures (73). A sharp significant increase in the expression levels of HlDnmt was observed after 9 days of cold exposure (4 • C).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the present study, the first 3 days of cold exposure were marked with a significant decrease in the expression levels of all the Dnmt genes but increased significantly with the prolongation of days of cold treatment. A similar trend was observed in the armyworm (Mythimna separata) where a decreased pattern of expression was observed after short exposures to various temperatures (73). A sharp significant increase in the expression levels of HlDnmt was observed after 9 days of cold exposure (4 • C).…”
Section: Discussionsupporting
confidence: 75%
“…Due to the vital role of DNA methyltransferases in different biological processes, the knockdown of DsDnmt, DsDnmt1, HlDnmt1, and HlDnmt was carried out to identify their functions by assessing the mortality rate after the exposure of D. silvarum and H. longicornis ticks to sublethal low temperatures of −22 and −14 • C, respectively, for 2 h. Interestingly, the mortality rates of the two tick species significantly increased which underscores the impact of DNA methyltransferases on the cold tolerance of ticks. This result was corroborated by the resultant significant mortality of armyworms (whose MsDnmt1 genes have been knocked down) after exposure to a low temperature (73). Previous studies have demonstrated the effect of extreme temperatures on arthropod development which include reduced fecundity, deformity, and mortality (77)(78)(79).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the northern armyworm (Mythimna separata), inhibition of Dnmt1 via RNAi negatively impacted larval development under elevated temperatures. 103 Comparably, RNAi silencing of Dnmt3 reduced heat and cold tolerance in the white fly (Bemisia tabaci), indicating that de novo methylation is associated with thermal stress responses. 90 Although DNA methylation may drive rapid responses to environmental stress, only a handful of insect studies have explored how DNA methylation is impacted by exposure to single stressors, let alone multiple stressors.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In de novo methylation, insect DNA methyltransferases appear to respond to temperature stress. In the northern armyworm ( Mythimna separata ), inhibition of Dnmt1 via RNAi negatively impacted larval development under elevated temperatures 103 . Comparably, RNAi silencing of Dnmt3 reduced heat and cold tolerance in the white fly ( Bemisia tabaci ), indicating that de novo methylation is associated with thermal stress responses 90 …”
Section: What Do We Know About Mechanisms Underlying Cross‐protection...mentioning
confidence: 99%